Modificações pós- traducionais das histonas H3K9ac e H4K12ac podem estar associadas com a patogênese das proliferações celulares na leucoplasia bucal. - Espinosa, Roberta Cristina Gomes (2018)
Background: Oral leukoplakia is the most prevalent potentially malignant disorder and the acknowledgement of molecular mechanisms involved in its development and progression to oral squamous cell carcinoma can provide novel biomarkers for determining prognosis and monitoring disease progression. . Among these, epigenetic alterations such as histone post-translational modifications have been targeted for investigation considering their roles in gene transcription, chromatin condensation and decondensation, DNA replication and repair, in which H3K9ac and H4K12ac play significant roles. The aim of this study was to analyze the expression of H3K9ac and H4K12ac in oral leukoplakia and its association with cell proliferation marker Ki-67 and clinical-pathological data. Methods: Samples of 50 cases of oral leukoplakia and 15 fragments of normal mucosa were submitted to immunohistochemical assay for H3K9ac, H4K12ac and Ki-67 expression. Quantitative analysis was performed measuring integrated optical density and percentage of positive nuclei. Results: Expression of H4K12ac in oral leukoplakia was significantly different from normal mucosa for both mean integrated optical density values (p = 0.007) and percentage of positive nuclei (p = 0.02) in comparison to control group. No association could be found among sociodemographic and clinical-pathological data. Ki-67 expression correlated positively with percentage of positive nuclei for H3K9ac (p < 0.0001) and with integrated optical density for both histone modifications (H3K9ac, p = 0.0007; H4K12ac, p = 0.002). Conclusion: The present findings suggest that H3K9ac and H4K12ac contribute to the development of oral leukoplakia by regulating epithelial cell proliferation mechanisms.